Penerapan Metode Pembelajaran Blended Learning Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Dan Budi Pekerti - Khoirul Nikmah Nikmah; Ramdanil Mubarok (Thawalib: Jurnal Kependidikan Islam, 2022)
Distance learning carried out during the Covid-19 pandemic left many problems in its implementation. Along with the increasingly controlled spread of Covid-19, it is possible to carry out face-to-face learning even though it is still limited to face-to-face learning. Limited face-to-face learning allows educational institutions to use blended learning methods. This study aims to improve the learning outcomes of Islamic religious education subjects and manners in reading the Qur'an. This research was carried out at SMA Negeri 1 Sangatta Utara in class XII IPA 6 in the odd semester in 2021/2022 with a total of 34 students. The method implemented in this research is Kurt Lewis' CAR model where the model is based on the components of planning, taking action, observing, and reflecting. The result is that the improvement of student learning outcomes can be done by applying blended learning model learning. This is done in Basic Competency 4.1.1, namely reading with correct makhorijul letters and tajwid in the Qur'an Surah Luqman (31); 13-14, and the Qur'an Surah Al-Baqarah (2): 83. The achievement of Cycle 1 was 32.3% then increased in cycle 2 to 91%.